Herschel observations of a z∼ 2 stellar mass selected galaxy sample drawn from the GOODS NICMOS Survey - Hilton, M; Conselice, C; Roseboom, I; Burgarella, D; Buat, V; Berta, S; Béthermin, M; Bock, J; Chapman, S; Clements, D; Conley, A; Conversi, L; et al. (2012)
We present a study of the far-infrared (IR) properties of a stellar mass selected sample of 1.5 < z < 3 galaxies with log(M */M ⊙) > 9.5 drawn from the Great Observatories Origins Deep Survey (GOODS) Near Infrared Camera and Multi-Object Spectrometer (NICMOS) Survey (GNS), the deepest H-band Hubble Space Telescope survey of its type prior to the installation of Wide Field Camera 3 (WFC3). We use far-IR and submm data from the Photoconductor Array Camera and Spectrometer (PACS) and Spectral and Photometric Imaging Receiver (SPIRE) instruments on-board Herschel, taken from the PACS Evolutionary Probe (PEP) and Herschel Multi-Tiered Extragalactic Survey (HerMES) key projects, respectively. We find a total of 22 GNS galaxies, with median log(M */M ⊙) = 10.8 and z = 2.0, associated with 250μm sources detected with signal-to-noise ratio (SNR) > 3. We derive mean total IR luminosity logL IR(L ⊙) = 12.36 ± 0.05 and corresponding star formation rate (SFR) IR + UV = (280 ± 40)M ⊙yr -1 for these objects, and find them to have mean dust temperature T dust ≈ 35K. We find that the SFR derived from the far-IR photometry combined with ultraviolet (UV)-based estimates of unobscured SFR for these galaxies is on average more than a factor of 2 higher than the SFR derived from extinction-corrected UV emission alone, although we note that the IR-based estimate is subject to substantial Malmquist bias. To mitigate the effect of this bias and extend our study to fainter fluxes, we perform a stacking analysis to measure the mean SFR in bins of stellar mass. We obtain detections at the 2-4σ level at SPIRE wavelengths for samples with log(M */M ⊙) > 10. In contrast to the Herschel detected GNS galaxies, we find that estimates of SFR IR + UV for the stacked samples are comparable to those derived from extinction-corrected UV emission, although the uncertainties are large. We find evidence for an increasing fraction of dust obscured star formation with stellar mass, finding SFR IR / SFR UV ∝M*0.7±0.2, which is likely a consequence of the mass-metallicity relation. © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.